CpG island methylator phenotype is an independent predictor of survival after curative resection for colorectal cancer: A prospective cohort study. Issue 8 (August 2017) - Kim, Chang Hyun; Huh, Jung Wook; Kim, Hyeong Rok; Kim, Young Jin
Abstract: Background and Aims: The CpG island methylator phenotype (CIMP) is found in approximately 30% of colorectal cancer (CRC) cases. However, the role of CIMP status in predicting oncologic outcomes in curatively resected CRC is still unclear. Study: Between January 2006 and December 2006, we retrospectively reviewed 157 consecutive patients who underwent curative surgery for CRC. Prognostic significance of CIMP status was evaluated using reverse transcriptase‐polymerase chain reaction. Results: CIMP‐high (H) and CIMP‐none/low (N/L) tumors were found in 50 cases (31.8%) and 107 cases (68.2%), respectively. CIMP‐H tumors were significantly associated with female sex, colonic location, poorly/mucinous histologic type, higher T category, perineural invasion, and MSI‐high status ( P = 0.001). During a median of 64.5 months, tumor recurrence developed in 47 (29.9%) patients. The 5‐year disease‐free survival for CIMP‐H and CIMP‐N/L was 61.4% and 76.3% ( P = 0.018). In addition, multivariate analysis showed that CIMP‐H was also a significant prognostic factor ( P = 0.042). When analysis was performed according to anatomical location, more marked survival differences were observed in patients with colon cancer ( P = 0.026) than in patients with rectal cancer ( P = 0.210). Similarly, the role of CIMP status as a prognostic indicator was more prominent in patients with stage I/II ( P = 0.006) than in patients with stage III/IV CRC ( P = 0.65). Conclusions: DNA methylation status can be considered as a useful predictor of survival after CRC surgery, particularly for patients with stage I/II disease or colon cancer.